Corporate Governance in Central and Eastern Europe: Transition management is a tough job - Debora Revoltella; Peter R. Haiss; Gerhard Fink (SUERF - The European Money and Finance Forum, 1998)
1) Financing Firms in East European Countries: An Asymmetric Information and Agency Costs Approach, by Debora Revoltella 2) Seven Years of Financial Market Reform in Central Europe, by Peter H. Haiss and Gerhard Fink.
Keywords: 330; Corporate governance; Corporate Governance; Systemtransformation; Osteuropa